THE PLACE OF THE POST-SOVIET SPACE IN THE FOREIGN POLICY PLANNING OF RUSSIA - EBZEEVA, Yulia (CENTRAL ASIA AND THE CAUCASUS, 2017)
To resolve the conflict-prone situation in the post-Soviet space and to be able to predict its further development, it is important to study the evolution of policies and political technologies used by Russia in respect to the post-Soviet countries. The general problem of technologies and practices of political influence in the foreign policy planning of modern Russia deserves public attention. In the twenty-first century, political communication, as well as the functions of political leaders, have undergone fundamental changes. In the middle of the second decade of the new century, communication in politics was, for the most part, a slow, one-sided process, mostly involving exchange of information. With the development of the mass media, citizens started receiving more and more opportunities for monitoring the actions of politicians, up until the mass media engaged in the competitive struggle for the interpretation of events. In some states, this struggle has started since the middle of the twentieth century, in others it is only escalating. In the electronic information era, each action of politicians potentially becomes the object of discussion for many segments of the population, in connection with which foreign policy planning is undergoing significant transformations. On the one hand, society receives an opportunity to control the actions of political leaders, to assess their actions through the media and to influence political decisions. On the other hand, in addition to the main responsibilities of a political leader in running a country, the task emerges, which is no less important—managing information. In connection with this, there appears a new type of foreign policy planning—a rhetorical one. If previously, a sensible and deliberative discourse in interaction with the elite was typical of the institutional leader, and his most important skills were the knowledge of the bureaucracy and the ability to make reasoned decisions, then for the “rhetorical” leader, the ability to persuade comes to the fore, and power is partly based on the popular image and people’s support. The loss of control over information flow can lead to a gradual loss of control over the state, and hence shift the center of political power. This fully applies to Russia, including the processes of its foreign policy planning in the post-Soviet space and the implementation of the plans already developed. The international environment and the internal situation in Russia influence foreign policy to varying degrees. Thus, the stronger became the state power, and more stable.